Freshwater plastisphere: a review on biodiversity, risks, and biodegradation potential with implications for the aquatic ecosystem health - Bocci, Valerio; Galafassi, Silvia; Levantesi, Caterina; Crognale, Simona; Amalfitano, Stefano; Congestri, Roberta; Matturro, Bruna; Rossetti, Simona; Di Pippo, Francesca (Frontiers in Microbiology, 2024)
The plastisphere, a unique microbial biofilm community colonizing plastic debris and microplastics (MPs) in aquatic environments, has attracted increasing attention owing to its ecological and public health implications. This review consolidates current state of knowledge on freshwater plastisphere, focussing on its biodiversity, community assembly, and interactions with environmental factors. Current biomolecular approaches revealed a variety of prokaryotic and eukaryotic taxa associated with plastic surfaces. Despite their ecological importance, the presence of potentially pathogenic bacteria and mobile genetic elements (i.e., antibiotic resistance genes) raises concerns for ecosystem and human health. However, the extent of these risks and their implications remain unclear. Advanced sequencing technologies are promising for elucidating the functions of plastisphere, particularly in plastic biodegradation processes. Overall, this review emphasizes the need for comprehensive studies to understand plastisphere dynamics in freshwater and to support effective management strategies to mitigate the impact of plastic pollution on freshwater resources.